Pengaruh Kenaikan Tarif PPN dan Sosualisasi Tarif PPN terhadap Daya Beli Masyarakat : (Studi Empiris Mayarakat Kecamatan Larangan Kabupaten Brebes) - Bela Dwi Defira; Dumadi, Dumadi; Nasiruddin, Nasiruddin; Roni, Roni (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Purchasing power is the ability of people to buy goods and services to meet their needs. This study aims to analyze the effect of increasing VAT rates and socialization of VAT rates on people's purchasing power. Sampling was obtained using purposive sampling technique, with a sample size of 400 respondents aged 20 years and over and already having jobs. The data analysis method used is data quality test (validity and reliability), classical assumption test (normality, multicollinearity, heteroscedasticity and autocorrelation) for hypothesis testing using multiple linear regression, partial significance test (t test), simultaneous test (F test) and cqoefficient of determination (R2). The results of the study indicate that there is an effect of increasing VAT rates and socialization of VAT rates partially and simultaneously on people's purchasing power.